HUMAN RESOURCES: THE IMPORTANCE OF QUALITY OF LIFE AT WORK IN YOUR SUB-DIVISION OF THE FEDERAL INSTITUTE OF AMAZONAS/IFAM CAMPUS EIRUNEPÉ - Xavier, Francisca das Chagas Estevão; de Souza, Maria Lins França; Cavalcanti, Patrícia Maria Moreira; Esquerdo, Cristina Sá; Magalhães, Cilene Farias Batista; Reis, Gustavo Costa; Belém , Romário Rodrigues; Muniz, Ramona Ramos de Oliveira (Seven Editora, 2025)
This article aimed to investigate the Quality of Life at Work (QVT) in a subunit of the Instituto Federal do Amazonas located in a region of difficult access in the Amazon. The institution in question serves approximately 600 students and has 40 teachers and 20 technical-administrative staff of secondary and higher education. The internship in the Human Resources (HR) area allowed us to observe an alarming picture of the health problems of these staff, when, in two years, there were 17 15-day medical certificates and 5 sick leaves in this Integrated Health Care Service (SIAS), all for psychological reasons, intrinsic to exhaustion such as depression, anxiety, burnout syndrome and other mental disorders. The data showed an increasing need to take care of the mental health of workers, especially in a teaching unit located in the Amazon region, which presents logistical, social and economic challenges. In this context, the study proposed the creation and application of a questionnaire to the HR sector to map where the main demands and dissatisfactions of employees with the work environment are. The QWL indicators contained in this questionnaire are recognized in the literature as organizational climate, interpersonal relationships, working hours, professional recognition and physical work environment. The theories that served as support were based on writers who deal with (QWL), such as Elton Mayo, (1933) Maslow, (1954) Herzberg, (1966) Oliveira, (2022) among others. With this result, we were able to create guidelines for the elaboration of a (QWL) policy aimed at reducing absences due to health issues and providing a productive, pleasant and healthy environment for the worker. DOI: https://doi.org/10.56238/sevened2025.026-009